Growth Performance, Antioxidant, and Teratogenic Activity of Panaeolus antillarum Submerged-cultured in Coconut Water Enriched with Ascorbic Acid (Biosaintifika: Journal of Biology & Biology Education, 2026)
Panaeolus antillarum is a mushroom commonly growing in animal dung, which has been identified to possess promising medicinal properties. This present study investigated the mycelial growth performance and bioactivities of Panaeolus antillarum in coconut water supplemented with varying concentrations of ascorbic acid. Methanolic extract of the culture-spent supplemented with the different amounts of ascorbic acid (0 mg, 5 mg, 10 mg, 15 mg) was used to determine the total phenolic contents (Folin-Ciocalteu), antioxidant (DPPH radical scavenging activity), cytotoxic activity, and teratogenic effects in zebra fish embryo. Statistical analysis revealed the highest mycelial yield in 0 mg (control) and 5 mg with 2.06 g and 1.92 g, respectively, while the lowest was recorded in 20 mg with 0.98 g. The highest volume loss was also registered in 0 mg (18.17 mL), which was significantly different from other concentrations.  Panaeolus antillarum with 20 mg of ascorbic acid obtained the highest phenolic content (313.76 mg AAE/g sample) and maximum radical scavenging activity (83.08%). Regardless of the presence of ascorbic acid, all culture-spent of P. antillarum exhibited a toxic effect after 36 hours, with 100% mortality. Furthermore, the varying amounts of P. antillarum affected zebra fish embryos hatchability. Growth retardation was the only noted teratogenic effect of the spent material. Hence, P. antillarum could be a promising source of natural bioactive compounds that can be further studied for the possible development of pharmaceutical drugs. With these beneficial effects, this study particularly supports the United Nations’ Sustainable Development Goals (SDGs) 3 and 15. Mushrooms are ecologically significant species in the forest and other land areas and are significantly utilized for the promotion of good health. Thus, conservation and protection of these species is necessary.